Case report: Disseminated Cladophialophora bantiana phaeohyphomycosis in a dog with hepatic dysfunction, and concurrent ehrlichiosis - Alonso, Flavio H.; Fenton, Heather; Muller, Ananda; Freeman, Mark A.; Becker, Anne A. M. J.; Rolph, Kerry; Abramo, Nicole; Rawlins, Gilda; Kitson, Liam; Kessel, Erica; Thrall, Mary Anna (Frontiers in Veterinary Science, 2024)
A 1-year-old mixed breed dog initially presented with marked ascites due to a low-protein transudate resulting from portal hypertension. Laboratory evaluation revealed non-regenerative anemia, lymphopenia, thrombocytopenia, laboratory evidence of hepatic insufficiency (hypoalbuminemia, decreased urea, increased post-prandial bile acids, prolonged activated partial thromboplastin time (aPTT)) and Ehrlichia canis infection. Approximately a week later, the dog was falling declining and was euthanized. On autopsy, multifocal hepatic granulomas and acquired portosystemic shunts (APSS) were seen. Imprint cytology revealed fungal hyphae and pyogranulomatous inflammation in the liver and brain. Disseminated Cladophialophora bantiana phaeohyphomycosis was diagnosed by histologic examination, culture and PCR.Immunosuppression due to ehrlichiosis is suspected to have predisposed this animal to fungal infectionImmunosuppression is suspected to have arisen from Rickettsial disease and predisposed fungal infection. To the authors' knowledge, this is the first report of C. bantiana in the West Indies.This case appears to be the first report of C. bantiana in the West Indies.